The Effect of Mathematical Disposition on Students' Mathematical Creative Thinking Abilities in Class XI - Thoyibi, Ali Imron; Sangco, Retchelle P. (International Journal of Research in Mathematics Education, 2023)
Mathematics as a lesson that is useful for the development of thinking, thinking becomes an important process in it, where students are expected to be able to think deductively. Students are asked to understand the concept of the material that has been delivered with an active and conscious attitude, or referred to as a disposition. The purpose of this research was to find out the effect of mathematical disposition on students' mathematical creative thinking abilities in class XI MIPA MAN 2 Banyumas. The population in this research were all students of class XI MIPA totaling 243 students, 153 students were taken as samples using simple random sampling technique. This research was conducted using quantitative research methods where data was obtained by distributing research instruments in the form of questionnaires and tests. The analysis technique uses a simple linear regression analysis technique. Before the analysis test was carried out, the data went through analysis prerequisite tests, namely the normality test, regression significance test, and linearity test. The results of this study indicate that there is an influence of mathematical disposition on students' mathematical creative thinking abilities of 12,6%. Also regression equation obtained, Ŷ=8.325+0.730X which shows that the regression coefficient value is positive, which means that if the mathematical disposition (X) increases by 1 unit, the student's mathematical creative thinking ability (Y) will increase by 0.730 units.